Literature review on business prototypes for digital platform - Shrutika Mishra; A. R. Tripathi (Journal of Innovation and Entrepreneurship, 2020)
In today's world, many digitally enabled start-ups are budding all over the globe because of the fast enhancement in digital technologies. For the establishment of new business, it is necessary to adopt a proper business model which needs to define the way in which the company will provide values and the ways in which the customers can pay for their services. This paper aims to study the various business models being used in today's marketplace and to provide a better understanding for these business models by having an insight on the attributes.
Keywords: 650; Business models; e-commerce; Digital marketplace; Start-ups; Digitalplatform